Telaah morfometrik Pinctada margaritifera untuk pengembangan usaha budidaya - Sumtaki, Karel; Kalesaran, Ockstan J. J.; Lumenta, Cyska (Universitas Sam Ratulangi, 2018)
This study aimed to analyze the size of shell length, shell width and total weight of Pinctada margaritifera shells, and water quality parameters for the aquaculture development. Morphometric measurements include: shell length (PC), and shell width (LC), shell weight (BT). The results showed that PC size 8 - 11.99 cm, LC 8 - 9.99 cm and BT 80 - 99.99 gram dominate the Arakan watersÂ while PC size 6 - 9.99 cm, LC 6 - 7.99 cm and BT 60 - 79.99 gram dominate the BahoiÂ waters. The results of water quality measurements in both locations are Bahoi waters, namely: 29-32oC, DO 7-8,5 mg/l, pH 7,8-7,9, salinity, 28-32 ppt, 4,5- 7 meters, 11 cm/sec. While in Arakan waters, the temperature was 30-30,8oC, DO 6,3-6,7 mg/l, pH 7,6-7,7 salinity 30 ppt, brightness 4-5 meter, current velocity 4,5 cm / second. Both locations were feasible for the development of pearl aquacultureKeywords: Morphometric, Pinctada margaritifera, Aquaculture